Multi‐modal optical imaging characterization of atherosclerotic plaques. Issue 10 (25th November 2015) - Gubarkova, Ekaterina V.; Dudenkova, Varvara V.; Feldchtein, Felix I.; Timofeeva, Lidia B.; Kiseleva, Elena B.; Kuznetsov, Sergei S.; Shakhov, Boris E.; Moiseev, Alexander A.; Gelikonov, Valentin M.; Gelikonov, Gregory V.; Vitkin, Alex; Gladkova, Natalia D.
Abstract : We combined cross‐polarization optical coherence tomography (CP OCT) and non‐linear microscopy based on second harmonic generation (SHG) and two‐photon‐excited fluorescence (2PEF) to assess collagen and elastin fibers and other vascular structures in the development of atherosclerosis, including identification of vulnerable plaques, which remains an important clinical problem and imaging application. CP OCT's ability to visualize tissue birefringence and cross‐scattering adds new information about the microstructure and composition of the plaque. However its interpretation can be ambiguous, because backscattering contrast may have a similar appearance to the birefringence related fringes. Our results represent a step towards minimally invasive characterization and monitoring of different stages of atherosclerosis, including vulnerable plaques. CP OCT image of intimal thickening in the human coronary artery. The dark stripe in the cross‐polarization channel (arrow) is a polarization fringe related to the phase retardation between two eigen polarization states. It is histologically located in the area of the lipid pool, however this stripe is a polarization artifact, rather than direct visualization of the lipid pool. Abstract : The information obtained by cross‐polarization optical coherence tomography (CP OCT), related to birefringence and cross‐scattering properties of arterial tissues, may improve the reliability and accuracy of the microstructural and compositional assessment of the different stages of atherosclerotic plaque. Moreover, the Pythagorean sum of the two CP OCT channels yields only the backscattering‐related contrast, thereby helping to separate real structures from polarization artifacts such as phase retardation fringes.